Evaluation of endurance training period in competitive swimming coaching - using lactate curve test - Tsubakimoto, S.; Kojima, K.; Shimoyama, Y.; Sengoku, Y.; Nimura, T. (Japanese Journal of Sciences in Swimming and Water Exercise, 2006)
This study used a lactate curve test to evaluate the endurance training period in competitive swimming coaching. Endurance training period was defined to two categories, as a general endurance period (6 weeks) and a specific endurance period (6 weeks). This study enrolled 10 well-trained male college swimmers. A lactate curve test was conducted before the general endurance period (Pre-Test), between the general and specific endurance period (Mid-Test), and after a specific endurance period (Post-Test). After the training volume at EN2 increased during the general endurance period, V@OBLA from the lactate curve test was improved significantly (p<0.05) from the Pre-test to the Mid-Test. At the specific endurance period, the ratio of training volume increased at higher intensities such as EN2 and EN3, but the training volume was decreased during the recovery week for swimming competition. It was suggested that the lactate curve indicated a tendency to shift lower from the Mid-Test to the Post-Test.